Social Media: A Channel to New Media Advertising (International Journal of Food and Nutritional Sciences, 2022)
Today's advertising is evolving due to the very real effects of globalisation, digitization, and social media. Numerous businesses and advertising players are compelled to use cutting-edge commercial techniques and new customer and company models. For the majority of businesses, social media marketing is now the norm. Through social media platforms like Twitter, Facebook, and YouTube, the marketing technique is applied. Social media marketing is able to engage and interact on a much more personalised and dynamic level than traditional marketing because it makes use of the social component of the web. Even though there are other marketing tactics available, only social media advertising can provide steady revenue right now